Design and analysis of a doubly salient wound field starter generator for cost-effective automobile application - Cai, Shun (2022)
Doubly salient wound field machines exhibit the advantages of robust structure and controllable flux, and hence have been utilized as generators in applications of automobiles and renewable energy. However, the inherent unbalanced phase back-electromotive force (EMF) waveform caused by the asymmetric flux path brings difficulties for precise control and smooth operation. To solve the problem caused by unbalanced back-EMF waveform in conventional doubly salient machines, this paper presents a novel doubly salient wound field machine with balanced and symmetrical back-EMF waveform as starter generator in automobile application. The robust structure and the controllable flux are inherited, while the magnetless feature makes it promising for cost-sensitive applications. The proposed machine can be operated as an assistant motor for torque boosting at start-up stage, as well as a power recycling generator for battery charging at steady state. It is revealed that the proposed wound field machine exhibits similar cost, comparable torque density, improved torque ripple, and higher efficiency than the switched reluctance machine. Finally, the proposed prototype is fabricated, and dynamic experiment is conducted to validate the feasibility for automobile starter generator application.